HUBUNGAN KESADARAN DAN PERILAKU KERJA APARATUR SIPIL NEGARA - Made Artama (Daiwi Widya, 2022)
AbstractBased on the world bank report, the level of effectiveness of the Indonesian government is in the 62nd position in the world. To increase the ranking, the State Civil Apparatus (SCA) has a very important role. In managing and improving the performance of SCA in serving the community, the Made Artama adalah seorang tenaga pendidik di SMA Negeri 1 Sukasada government has issued various policies and legal products aimed at forming SCA who have integrity, are professional, neutral and free from political intervention, free from corruption, collusion and nepotism practices, and are able to provide public services for the community and are able to carry out its role as an adhesive element for the unity and integrity of the nation. However, based on several community satisfaction survey reports, most SCA behavior received low ratings. Corruption, collusion and nepotism, political intervention, the practice of buying and selling positions to the development of radical understanding among SCA are examples of SCA behavior that needs to be corrected. Several studies in the field of education prove that increased awareness can increase learning ability, increase mind-body coordination, increase organizational ability and efficiency, increase energy and dynamism, better personality integration, reduce negative personality, and growth of ideal social behavior. This study aimed at finding out how the relationship between awareness and SCA work behavior. The results of the study showed that awareness had a positive correlation with SCA behavior. The higher the level of awareness, the better SCA behavior will be.Keywords: government effectiveness, community satisfaction, awareness, work behavior